TEACHING VOCABULARY THROUGH THE CONCEPT ATTAIMENT MODEL AT SMP IT ANNAJIYAH LUBUKLINGGAU - Sri Wulandari; Ayu Oktaviani; Yulfi Yulfie (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2021)
ABSTRACT The problem of this research was “is it significantly effective to teach vocabulary through the Concept Attainment Model (CAM) at SMP IT Annajiyah Lubuklinggau in academic year 2019/2020?” The objective of this research was to find out whether or not it is significantly effective to teach vocabulary through the Concept Attainment Model (CAM) at SMP IT Annajiyah Lubuklinggau in academic year 2019/2020. The population of this research was all of the seventh grades consist of 43 students of SMP IT Annajiyah Lubuklinggau in academic year 2019/2020 and total number of sample was 18 students from VIII.A. The sample in this research was taken through cluster random sampling. In this research, the researcher used pre-experimental method. In collecting the data, the researcher used written test. In analyzing the data, the researcher used three techniques. They were: individual score, normality test and matched t-test. Based on the result of the data analysis, the researcher found out that the students’ average score was 59.166 in the pre-test and it increased in the post-test which score was 78.888. The result of matched t-test was 7.498, while ttable was 1.734. It means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Furthermore, it was significantly effective to teach vocabulary through the Concept Attainment Model (CAM) at SMP IT Annajiyah Lubuklinggau in academic year 2019/2020.